Perlindungan Hukum atas Kebocoran Data Pribadi Konsumen pada Perdagangan Elektronik Lokapasar (Marketplace) - Kadek Dio Ramadi Natha; Nyoman Putu Budiartha; Ni Gusti Ketut Sri Astiti (Warmadewa Press, 2022)
A growing global economy supported by technological advances has resulted in the birth of a new market, namely a place for electronic commerce known as a marketplace. Marketplace as an intermediary that facilitates interaction between sellers and buyers, including supporting transaction activities. Marketplace users are required to have an account containing personal data. Advances in technology are now raising new problems, such as related to personal data security. The purposes of this study are to find out the legal protection against the leakage of consumer personal data related to electronic commerce based on the rules of law in Indonesia and the resolution of disputes over the case of leakage of consumer personal data in electronic trading of marketplace users. This study uses a normative research type with a case, legislation, and conceptual approach. Data collection techniques were carried out using documentation techniques and library techniques. Sources of legal materials used in the form of primary and secondary legal sources. The analysis technique is done by interpretation and qualitative. The findings reveal that legal protection for personal data leakage is still weak because it does not yet have a legal umbrella specifically regulating it, but in the case of consumer data leakage in electronic commerce there are several existing laws and regulations that are used as a reference to resolve disputes over cases of leakage of user's personal data.